POTENSI AKAL MANUSIA DALAM AL QUR-AN DAN RELEVANSINYA DENGAN PENDIDIKAN ISLAM - Suswanto; Firmansyah (Prodi Pendidikan Agama Islam Sekolah Tinggi Agama Islam Daruttaqwa Gresik, 2021)
Man who has the provision of reason is not enough to be said to be a noble being as its form (physical). Because, there can be a reality if humans are not able to function the mind properly and correctly, then the high degree desired cannot be realized. Man can be said to be human if he has reason and uses that sense as he should. That's why, the position of reason is put above the same and the mind. Through reason, there arises competence (ability) to reach the understanding of something that ends in the possession of noble ethics (morals). Something like this can be said to be a driving sense.